Altered plasma levels of arginine metabolites in depression - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
L-Arginine pathway metabolites appear to play differential roles in the pathogenesis of major depressive disorder (MDD). Studies have revealed an antidepressant and anxiolytic effect of agmatine and putrescine. Possible mechanisms of these effects include inhibition of nitric oxide synthase and N-methyl-D-aspartate receptors. The present study sought to determine whether MDD is associated with altered levels of arginine metabolites and whether these metabolites are associated with depression, anxiety and stress severity. Seventy seven MDD patients 21-65 years of age with a minimum score of 18 on the Hamilton Depression Scale, and 27 age and sex matched healthy controls (HC) were included. Patients with uncontrolled physical diseases, abnormal routine lab tests, other psychiatric diagnoses, or under psychotropic medication were excluded. HC subjects were recruited from the community. Rating instruments included Hamilton Depression and Anxiety Scales, Beck Depression and Anxiety Inventory and Perceived Stress Scale. Fasting blood was drawn between 8:30 and 11:00 a.m. and High Performance Liquid Chromatography (HPLC) was used to measure plasma arginine metabolites. ADMA (Asymmetrical dimethylarginine) and putrescine were significantly lower while SDMA (Symmetric dimethylarginine), agmatine and ornithine were significantly higher in MDD patients (p(<)0.05). Depression, anxiety and stress severity were negatively correlated with ADMA and putrescine (p(<)0.05). Stress was positively correlated with citrulline, NOHA (N-omega-hydroxy-nor-1-arginine), SDMA, agmatine and ornithine (p(<)0.05). Lower putrescine levels predicted depression diagnosis (p = 0.039) and depression severity (p = 0.003). Low ADMA level predicted depression severity as well. Arginine pathway metabolites are associated with the pathophysiology of depression. Putrescine may be a biomarker to predict MDD.
Keywords: Major depression; Stress; Arginine metabolites; Agmatine; Putrescine; ADMA (Asymmetric dimethyl arginine); FORCED SWIMMING TEST; ANTIDEPRESSANT-LIKE; ASYMMETRIC DIMETHYLARGININE; OXIDATIVE STRESS; NITRIC-OXIDE; IMIDAZOLINE RECEPTORS; COGNITIVE IMPAIRMENT; AGMATINE; BEHAVIOR; MICE